2015
DOI: 10.5194/piahs-372-39-2015
|View full text |Cite
|
Sign up to set email alerts
|

New information on regional subsidence and soil fracturing in Mexico City Valley

Abstract: Abstract. In this paper, updated information about regional subsidence in Mexico City downtown area is presented. Data obtained by R. Gayol in 1891, are compared with information obtained recently from surveys using the reference points of Sistema de Aguas de la Ciudad de México (2008) and on the elevation of a cloud of points on the ground surface determined using Light Detection and Ranging (LiDAR) technology. In addition, this paper provides an overview of recent data obtained from systematic studies focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The subsidence in CDMX, first reported in 1925 (Carrillo, 1947; Gayol, 1925), caused differential settlements in the colonial and modern structures. The area's leveling data from 1898 to 2005 shows constant land subsidence during the whole period (Auvinet et al., 2013), with a maximum subsidence of 40 cm/yr during 1998–2002. Recent studies used Interferometric Synthetic Aperture Radar (InSAR) and found large subsidence rates of 30 cm/yr within the city for 2007–2011 (Chaussard et al., 2014), ∼35 cm/yr for 2014–2021 (Chaussard et al., 2021), and ∼45 cm/year for 2019–2020 (Cigna & Tapete, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsidence in CDMX, first reported in 1925 (Carrillo, 1947; Gayol, 1925), caused differential settlements in the colonial and modern structures. The area's leveling data from 1898 to 2005 shows constant land subsidence during the whole period (Auvinet et al., 2013), with a maximum subsidence of 40 cm/yr during 1998–2002. Recent studies used Interferometric Synthetic Aperture Radar (InSAR) and found large subsidence rates of 30 cm/yr within the city for 2007–2011 (Chaussard et al., 2014), ∼35 cm/yr for 2014–2021 (Chaussard et al., 2021), and ∼45 cm/year for 2019–2020 (Cigna & Tapete, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…during the whole period (Auvinet et al, 2013), with a maximum subsidence of 40 cm/yr during 1998-2002. Recent studies used Interferometric Synthetic Aperture Radar (InSAR) and found large subsidence rates of 30 cm/ yr within the city for 2007-2011 (Chaussard et al, 2014), ∼35 cm/yr for 2014-2021 (Chaussard et al, 2021), and ∼45 cm/year for 2019-2020 (Cigna & Tapete, 2022). The subsidence has damaged infrastructure, and disturbed water and wastewater drainage systems.…”
mentioning
confidence: 99%
“…Una grieta se puede iniciar a consecuencia de cualquier condición que genere esfuerzos de tensión importantes en el suelo (Auvinet, 2010;Auvinet et al, 2013aAuvinet et al, , 2013bAuvinet et al, , 2017Auvinet et al, , 2018. Ciertos mecanismos como el fracturamiento hidráulico facilitan la generación y propagación de las grietas.…”
Section: Introductionunclassified